Method for preparing inorganic carbon composite sodium ferric sulfate positive electrode material with assistance of reduced iron powder and sodium ion battery

By using reduced iron powder to reduce trivalent iron to divalent iron during the sintering process of sodium electropositive electrode material, and using inorganic carbon source as conductive agent, the poor conductivity problem caused by incomplete decomposition of organic carbon sources is solved, and high The preparation of the properties of sodium ferrosulfate cathode material is suitable for large-scale production.

CN119320174AActive Publication Date: 2025-01-17HUNAN NANENG TIMES TECH DEV CO LTD

Patent Information

Application Number
CN202411446780.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

During the sintering process, the existing sodium electropositive electrode material, sodium ferric sulfate, is incompletely decomposed by the organic carbon source, resulting in poor conductivity and heterogeneous phase generation, which limits its electrochemical performance.

Method used

Use reduced iron powder to assist in the preparation of inorganic carbon composite sodium iron sulfate positive electrode material. By reducing trivalent iron to divalent iron during the stirring process, and using an inorganic carbon source as a conductive agent, it avoids the generation of miscellaneous phases during the sintering process and improves the material. conductivity and electrochemical properties.

Benefits of technology

The preparation of pure-phase sodium ferrosulfate positive electrode material with high electronic conductivity is achieved, which improves the electrochemical performance and cycle stability of the material, simplifies the preparation process, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320174A_ABST
    Figure CN119320174A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and mainly relates to a method for preparing an inorganic carbon composite sodium ferric sulfate positive electrode material under the assistance of reduced iron powder and a sodium ion battery. The method comprises the following steps: adding sodium sulfate, ferrous sulfate and reduced iron powder into deionized water, stirring until the sodium sulfate and the ferrous sulfate are completely dissolved, and separating the residual reduced iron powder to obtain a sodium ferric sulfate precursor solution; mixing the sodium ferric sulfate precursor solution with an inorganic carbon source, stirring, and carrying out spray drying to obtain an inorganic carbon composite sodium ferric sulfate positive electrode material precursor; and sintering the precursor in an inert atmosphere to obtain the inorganic carbon composite sodium ferric sulfate positive electrode material. According to the method, ferric iron is reduced into ferrous iron with electrochemical activity by using the reducing iron powder, and the inorganic carbon source is used as the conductive agent, so that the problem of poor conductivity of the material caused by incomplete decomposition of the organic carbon source in the sintering process is avoided, the pure-phase sodium ferric sulfate positive electrode material with high conductivity is synthesized and prepared, and the electrochemical performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and mainly relates to a method for preparing an inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reduced iron powder and a sodium ion battery. Background Art

[0002] Under the background of dual carbon, the new energy materials industry is booming. Compared with traditional batteries, lithium-ion batteries (LIBs) have the advantages of high energy density, long cycle life and high safety, and have been widely used in small portable electronic devices. However, in large-scale energy storage applications such as fixed energy storage systems with low power density requirements, large energy storage devices require a lot of lithium elements. The low lithium content in the earth's crust (0.0017%), high cost and uneven distribution have become factors limiting the development of lithium batteries. Therefore, it is necessary to find another low-cost alternative. Due to the abundant sodium resources, easy access and low cost, the development of sodium ion batteries (SIBs) has received more and more attention. Among them, the polyanion positive electrode material Na x M y (X a O b ) z D w , (M=one or more of Ti, V, Cr, Ni, Mn, Fe, Co, Cr, etc.); X is S, P, Si, W, etc.; Z is F and OH, etc. Due to its good structural stability, high operating voltage, simple structure, environmental friendliness, and easy synthesis, it has received widespread attention and has high application potential.

[0003] Na x Fe 3-0.5x As a new type of sodium cathode material, (SO4)3 has been favored by a large number of energy storage researchers due to its high structural stability, good long cycle performance and high operating voltage. In the study of sodium iron sulfate cathode materials, the ferrous ions present in it are easily oxidized into trivalent iron ions by air during the dissolution process, thereby losing electrochemical activity, and the poor conductivity of the material itself also limits its further development. In the preparation process of conventional polyanion materials, an organic carbon source is added. During the high-temperature sintering process, the organic carbon source decomposes to form a reducing gas that converts Fe 3+ Transformed into Fe 2+ However, the sintering temperature of sodium iron sulfate material is low, the organic carbon source cannot be completely decomposed during the sintering process, the carbonization effect is poor, and it is difficult to effectively reduce Fe 3+ , which results in the presence of impurities in the prepared sodium iron sulfate material and poor electrochemical performance of the material. Summary of the invention

[0004] In order to overcome the problems in the prior art, the present invention provides a method for preparing an inorganic carbon source composite sodium ferric sulfate positive electrode material with the assistance of reduced iron powder, wherein the reducing iron powder is used to reduce the non-electrochemically active trivalent iron to electrochemically active divalent iron during the raw material stirring process, and then an inorganic carbon source is used as a conductive agent to avoid the problem of poor material conductivity caused by incomplete decomposition of the organic carbon source during the sintering process, thereby synthesizing a pure phase sodium ferric sulfate positive electrode material with high electronic conductivity, thereby improving the electrochemical performance of the material.

[0005] In an embodiment of the present invention, the present invention provides a method for preparing an inorganic carbon composite sodium iron sulfate positive electrode material assisted by reduced iron powder, the method comprising the following steps:

[0006] S1. Add sodium sulfate, ferrous sulfate and reduced iron powder into deionized water, stir until the sodium sulfate and ferrous sulfate are completely dissolved, and separate the remaining reduced iron powder to obtain a sodium ferric sulfate precursor solution;

[0007] S2, mixing the sodium ferric sulfate precursor solution with an inorganic carbon source, stirring and then spray drying to obtain an inorganic carbon composite sodium ferric sulfate positive electrode material precursor;

[0008] S3. Sintering the inorganic carbon composite sodium ferric sulfate positive electrode material precursor in an inert atmosphere to obtain an inorganic carbon composite sodium ferric sulfate positive electrode material.

[0009] In an optional embodiment, the molar ratio of the reduced iron powder to ferrous sulfate is 0.0001 to 0.005:1.

[0010] In an optional embodiment, the inorganic carbon source is one or more of water-based carbon nanotube slurry, water-based graphene slurry, and water-based graphene nanoribbon slurry; and the solid content of the slurry is 5-15%.

[0011] In an optional embodiment, the mass ratio of inorganic carbon to sodium ferric sulfate in the inorganic carbon composite sodium ferric sulfate positive electrode material is 0.001-0.05:1.

[0012] In an optional embodiment, the concentration of the sodium iron sulfate precursor solution is 0.1-1.5 mol / L.

[0013] In an optional embodiment, the process parameters of the spray drying process are: the induced draft fan frequency is 20-50 Hz, the feed frequency is 5-15 Hz, the atomizer frequency is 200-400 Hz, the inlet air temperature is 200-280°C, and the outlet air temperature is 100-120°C.

[0014] In an optional embodiment, the sintering process in step S3 is:

[0015] In an inert atmosphere, the temperature is raised from room temperature to 300-450°C at a heating rate of 1-5°C / min and sintered for 8-12 hours.

[0016] Based on the same inventive concept, the present invention also provides a carbon composite sodium iron sulfate positive electrode material prepared by the above method, whose chemical formula is Na x Fe 3-0.5x (SO4)3 / C, wherein 2≤x≤2.8. The carbon composite sodium iron sulfate positive electrode material is a solid microsphere with a particle size of 10 to 30 μm.

[0017] An embodiment of the present invention further provides a sodium ion battery, wherein the positive electrode material of the sodium ion battery includes the above-mentioned carbon composite sodium iron sulfate positive electrode material.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a method for preparing an inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reducing iron powder; on the one hand, the reducing property of the reducing iron powder is used to provide a good reducing environment for the sodium ferric sulfate positive electrode material precursor without introducing other impurities, ensuring that no non-electrochemically active trivalent iron ions are produced during the preparation process; on the other hand, there is no non-electrochemically active trivalent iron ion impurities, and the generation of impurities is avoided in the subsequent sintering process. At the same time, an inorganic carbon source is used as a conductive agent to avoid the problem of poor conductivity of the material caused by incomplete decomposition of the organic carbon source during the sintering process. The specific process includes the steps of solution preparation, filtration, spray drying and sintering. The synthesis method is simple, the synthesis cycle is short, the raw materials are easily available, and it is easy to operate, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is a SEM image of the inorganic carbon composite sodium iron sulfate positive electrode material prepared with the assistance of iron powder in Example 1;

[0022] Figure 2 X-ray diffraction patterns of the inorganic carbon composite sodium ferric sulfate positive electrode material prepared with the assistance of iron powder in Example 1 and the carbon composite sodium ferric sulfate positive electrode material prepared in Comparative Example 1;

[0023] Figure 3The Fe 2p spectra of the inorganic carbon composite sodium ferric sulfate positive electrode material (a) prepared with the assistance of iron powder in Example 1 and the carbon composite sodium ferric sulfate positive electrode material (b) prepared in Comparative Example 1;

[0024] Figure 4 The first cycle charge and discharge curves of the button cell assembled with the inorganic carbon composite sodium ferric sulfate positive electrode material prepared with the assistance of iron powder in Example 1 and the carbon composite sodium ferric sulfate in Comparative Example 1 at a current rate of 0.1C at a voltage of 2 to 4.5V;

[0025] Figure 5 This is a cycle curve diagram of the button cell assembled with the inorganic carbon composite sodium ferric sulfate positive electrode material prepared with the assistance of iron powder in Example 1 and the carbon composite sodium ferric sulfate positive electrode material in Comparative Example 1 at a voltage of 2 to 4.5 V and a 1C rate. DETAILED DESCRIPTION

[0026] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0027] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0029] The method for preparing an inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reduced iron powder of the present invention specifically comprises the following steps:

[0030] Sodium sulfate, ferrous sulfate and reduced iron powder are added to a reactor filled with deionized water in a certain proportion and stirred thoroughly. After sodium sulfate and sodium ferrous sulfate are completely dissolved, the reduced iron powder is separated to obtain a sodium ferrous sulfate precursor solution; wherein sodium sulfate includes any one or two of anhydrous sodium sulfate and sodium sulfate decahydrate, and ferrous sulfate is one or more of ferrous sulfate monohydrate, ferrous sulfate pentahydrate, and ferrous sulfate heptahydrate, more preferably ferrous sulfate heptahydrate. The reduced iron powder is an iron element powder, and the molar ratio of the amount of reduced iron powder added to the amount of ferrous sulfate added is 0.0001 to 0.005:1, more preferably 0.001:1. The reduced iron powder is mainly used to reduce Fe in the solution. 3+ , while providing a reducing environment to prevent Fe 2+ In this reaction system, if the content of reduced iron powder is too high, it will be difficult to separate it from the solution, and if it is too low, the reducing property will be weak and it will not be able to prevent Fe 2+Oxidation, that is, the reduced iron powder can control the generation of non-electrochemically active trivalent iron ions, and there is no need to add other reducing agents to ensure a reducing atmosphere. The separation is simple, the introduction of other impurities is avoided, and the operation is simpler. The concentration of sodium sulfate is 0.5-1.5 mol / L; the concentration of ferrous sulfate is 1.5-2.5 mol / L, and the molar ratio of sodium sulfate to ferrous sulfate is (0.5-1):1. The concentration of the sodium ferric sulfate precursor solution is 0.5-2 mol / L, and more preferably 1.3 mol / L.

[0031] The sodium ferric sulfate precursor solution is mixed with an inorganic carbon source, and spray dried after stirring to obtain an inorganic carbon composite sodium ferric sulfate positive electrode material precursor. In the process, the inorganic carbon source is one or more of an aqueous carbon nanotube slurry, an aqueous graphene nanoribbon slurry, and an aqueous acetylene black slurry, preferably an aqueous carbon nanotube slurry; the solid content of the aqueous carbon nanotube slurry is 1 to 20%, and more preferably 5%. For the solid content of the inorganic carbon source, when it is too high, the consistency and stability of the slurry will be poor, and it is easy to agglomerate into a gel state, which is not conducive to later use; if the solid content is too low, the solid content of the entire system will be reduced, affecting the particle size and integrity of the material, while reducing production capacity. In addition, the amount of the added inorganic carbon source is 0.001 to 0.05: 1. The excessive addition of the inorganic carbon source will reduce the proportion of active substances in the material system, while increasing the material production cost. The addition of too low a material conductivity is low, and the electrochemical performance cannot be effectively exerted. During the spray drying process of this step, the induced draft fan frequency of the spray drying equipment is 20-50 Hz, more preferably 35 Hz; the atomization frequency of the atomizer is 200-400 Hz, more preferably 350 Hz; the inlet air temperature is 200-280°C, more preferably 225°C; and the outlet air temperature is 90-130°C, more preferably 120°C.

[0032] The sodium iron sulfate cathode material precursor is sintered in an inert atmosphere to obtain an inorganic carbon composite sodium iron sulfate cathode material. During calcination, the material is first ventilated for 120 minutes under the protection of a protective atmosphere such as nitrogen or argon, and then the temperature is raised from room temperature to 300-500°C at a heating rate of 1-5°C / min, and calcined for 8-12 hours. This calcination step allows the sodium iron sulfate precursor to be further dehydrated, and at the same time, the crystal structure defects disappear, forming a spherical sodium iron sulfate cathode material with a good crystal structure. If the above sintering temperature is too high, the sulfate ions in the sodium iron sulfate will decompose, resulting in the formation of impurities in the sodium iron sulfate cathode material, and the cycle performance and rate performance of the material will decrease; if the sintering temperature is too low, the material will have a low degree of crystallinity, which may also lead to the formation of impurities, resulting in poor electrochemical performance of the material.

[0033] The present invention does not use the addition of an organic carbon source to provide a reducing atmosphere to the precursor solution and increase the conductivity of the material after sintering, but improves the conductivity of the polyanionic sodium ferric sulfate material by adding an inorganic carbon source with better conductivity, controls the reducing environment of the precursor solution by adding reducing iron powder, prepares a sodium ferric sulfate precursor with uniform structure and good morphology by spray drying, and successfully synthesizes a reducing iron powder to assist in the preparation of an inorganic carbon composite sodium ferric sulfate positive electrode material after high-temperature calcination. Specifically, the reducing iron powder used in the present invention is used as a reducing agent to provide a reducing environment for the mixed solution of ferrous sulfate and sodium sulfate without introducing other impurities, ensuring that the sodium ferric sulfate precursor material prepared by subsequent spray drying does not produce trivalent iron ions without electrochemical activity, thereby effectively improving the material's first discharge specific capacity, cycle stability and rate performance.

[0034] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.

[0035] Example 1

[0036] A method for preparing an inorganic carbon composite sodium ferric sulfate positive electrode material with the aid of reduced iron powder comprises the following steps:

[0037] Take 0.5g of reduced iron powder and put it into 1.5L of deionized water and stir at a stirring speed of 450rpm; add anhydrous sodium sulfate: ferrous sulfate heptahydrate into the deionized water with the reduced iron powder in a molar ratio of 1.3:1.7, and continue stirring during the addition process at a speed of 500rpm. After the anhydrous sodium sulfate and ferrous sulfate heptahydrate are completely dissolved in water, filter out the excess reduced iron powder to obtain a 1.3mol / L sodium iron sulfate precursor solution.

[0038] The aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution according to the ratio of inorganic carbon content to sodium iron sulfate 1%wt, and the magnetic stirrer was rotated at 500rpm and stirred for 30min. The inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.6 Fe 1.7 (SO4)3·xH2O / CNTs (x=7-17). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 12Hz, the atomizer frequency is 350Hz, the induced draft fan frequency is 35Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 500rpm.

[0039] The inorganic carbon composite sodium ferric sulfate positive electrode material precursor obtained above was first ventilated for 120 minutes under the protection of a nitrogen atmosphere to ensure that the air in the tubular furnace was discharged; then, under the protection of a nitrogen atmosphere, the temperature was raised from room temperature to 350°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a reducing iron powder-assisted preparation of an inorganic carbon composite sodium ferric sulfate positive electrode material powder.

[0040] Example 2

[0041] A method for preparing an inorganic carbon composite sodium ferric sulfate positive electrode material with the aid of reduced iron powder comprises the following steps:

[0042] Take 0.5g of reduced iron powder and put it into 1.5L of deionized water and stir at a stirring speed of 450rpm; add anhydrous sodium sulfate: ferrous sulfate heptahydrate into the deionized water with the reduced iron powder in a molar ratio of 1.25:1.75, and continue stirring during the addition process at a speed of 500rpm. After the anhydrous sodium sulfate and ferrous sulfate heptahydrate are completely dissolved in water, filter out the excess reduced iron powder to obtain a 1.3mol / L sodium iron sulfate precursor solution.

[0043] The aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution according to the ratio of inorganic carbon content to sodium iron sulfate 1%wt, and the magnetic stirrer was rotated at 500rpm and stirred for 30min. The inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.5 Fe 1.75 (SO4)3·xH2O / CNTs (x=7-17). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 12Hz, the atomizer frequency is 350Hz, the induced draft fan frequency is 35Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 500rpm.

[0044] The inorganic carbon composite sodium ferric sulfate positive electrode material precursor obtained above was first ventilated for 120 minutes under the protection of a nitrogen atmosphere to ensure that the air in the tubular furnace was discharged; then, under the protection of a nitrogen atmosphere, the temperature was raised from room temperature to 350°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a reducing iron powder-assisted preparation of an inorganic carbon composite sodium ferric sulfate positive electrode material powder.

[0045] Example 3

[0046] A method for preparing an inorganic carbon composite sodium ferric sulfate positive electrode material with the aid of reduced iron powder comprises the following steps:

[0047] Take 0.5g of reduced iron powder and put it into 1.5L of deionized water and stir at a stirring speed of 450rpm; add anhydrous sodium sulfate: ferrous sulfate heptahydrate into the deionized water with the reduced iron powder in a molar ratio of 1.3:1.7, and continue stirring during the addition process at a speed of 500rpm. After the anhydrous sodium sulfate and ferrous sulfate heptahydrate are completely dissolved in water, filter out the excess reduced iron powder to obtain a 1.3mol / L mixed sodium iron sulfate precursor solution.

[0048] The aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution according to the ratio of inorganic carbon content to sodium iron sulfate 1%wt, and the magnetic stirrer was rotated at 500rpm and stirred for 30min. The inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.6 Fe 1.7 (SO4)3·xH2O / CNTs (x=7-17). The inlet air temperature of the spray drying is 235°C, the outlet air temperature is 120°C, the feed frequency is 12Hz, the atomizer frequency is 350Hz, the induced draft fan frequency is 35Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 500rpm.

[0049] The inorganic carbon composite sodium ferric sulfate positive electrode material precursor obtained above was first ventilated for 120 minutes under the protection of a nitrogen atmosphere to ensure that the air in the tubular furnace was discharged; then, under the protection of a nitrogen atmosphere, the temperature was raised from room temperature to 350°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a reducing iron powder-assisted preparation of an inorganic carbon composite sodium ferric sulfate positive electrode material powder.

[0050] Example 4

[0051] A method for preparing an inorganic carbon composite sodium ferric sulfate positive electrode material with the aid of reduced iron powder comprises the following steps:

[0052] Take 0.5g of reduced iron powder and put it into 1.5L of deionized water and stir at a stirring speed of 450rpm; add anhydrous sodium sulfate: ferrous sulfate heptahydrate into the deionized water with the reduced iron powder in a molar ratio of 1.3:1.7, and continue stirring during the addition process at a speed of 500rpm. After the anhydrous sodium sulfate and ferrous sulfate heptahydrate are completely dissolved in water, filter out the excess reduced iron powder to obtain a 1.3mol / L sodium iron sulfate precursor solution.

[0053] The aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution according to the ratio of inorganic carbon content to sodium iron sulfate 0.5%wt, and the magnetic stirrer was rotated at 500rpm for 30min. The inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.6 Fe 1.7(SO4)3·xH2O / CNTs (x=7-17). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 12Hz, the atomizer frequency is 350Hz, the induced draft fan frequency is 35Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 500rpm.

[0054] The inorganic carbon composite sodium ferric sulfate positive electrode material precursor obtained above was first ventilated for 120 minutes under the protection of a nitrogen atmosphere to ensure that the air in the tubular furnace was discharged; then, under the protection of a nitrogen atmosphere, the temperature was raised from room temperature to 350°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a reducing iron powder-assisted preparation of an inorganic carbon composite sodium ferric sulfate positive electrode material powder.

[0055] Comparative Example 1

[0056] A method for preparing an inorganic carbon composite sodium iron sulfate positive electrode material without the aid of iron powder comprises the following steps:

[0057] Anhydrous sodium sulfate: ferrous sulfate heptahydrate were added into 1.5 L of deionized water in a molar ratio of 1.3:1.7 to prepare a 1.3 mol / L sodium ferric sulfate precursor solution.

[0058] According to the ratio of inorganic carbon content to sodium iron sulfate 1%wt, add aqueous carbon nanotube slurry with solid content of 5% to the above precursor solution, stir at a magnetic stirrer speed of 500rpm for 30min. The iron-free powder-assisted inorganic carbon composite sodium iron sulfate cathode material precursor solution is spray dried by spray drying. The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 12Hz, the atomizer frequency is 350Hz, and the induced draft fan frequency is 35Hz. The precursor solution should be continuously stirred while feeding, and the stirring speed is 500rpm. After spray drying, the spray-dried sodium iron sulfate cathode material precursor Na 2.6 Fe 1.7 (SO4)3·xH2O / VC / CNTs (x=7~17).

[0059] The above iron-free powder assisted inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.6 Fe 1.7 (SO4)3·xH2O / VC / CNTs (x=7~17) was first ventilated for 120 minutes under the protection of a nitrogen atmosphere to ensure that the air in the tube furnace was discharged; then, the temperature was raised from room temperature to 350°C at a heating rate of 5°C / min under the protection of a nitrogen atmosphere, and calcined for 10 hours to obtain an iron-free inorganic carbon composite sodium iron sulfate positive electrode material powder.

[0060] Comparative Example 2

[0061] A method for preparing a carbon composite sodium iron sulfate positive electrode material with the aid of a reducing organic carbon source comprises the following steps:

[0062] Take 0.5g of ascorbic acid and put it into 1.5L of deionized water and stir at a stirring speed of 450rpm; add anhydrous sodium sulfate: ferrous sulfate heptahydrate into the deionized water with ascorbic acid in a molar ratio of 1.3:1.7 to prepare a 1.3mol / L mixed sodium ferric sulfate precursor solution, and stir continuously during the addition process at a rotation speed of 500rpm.

[0063] According to the ratio of inorganic carbon content to sodium iron sulfate 1%wt, add water-based carbon nanotube slurry with a solid content of 5% to the above precursor solution, and stir for 30 minutes at a magnetic stirrer speed of 500rpm. The inlet air temperature of the spray drying is 225℃, the outlet air temperature is 120℃, the feed frequency is 12Hz, the atomizer frequency is 350Hz, and the induced draft fan frequency is 35Hz. The precursor solution should be continuously stirred while feeding, and the stirring speed is 500rpm. After spray drying, the inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.6 Fe 1.7 (SO4)3·xH2O / VC / CNTs (x=7~17).

[0064] The carbon composite sodium iron sulfate cathode material precursor Na 2.6 Fe 1.7 (SO4)3·xH2O / VC / CNTs (x=7~17) was first ventilated for 120 minutes under the protection of a nitrogen atmosphere to ensure that the air in the tube furnace was discharged; then, the temperature was raised from room temperature to 350°C at a heating rate of 5°C / min under the protection of a nitrogen atmosphere, and calcined for 10 hours to obtain a reducing organic carbon source-assisted preparation of a carbon-composite sodium iron sulfate positive electrode material powder.

[0065] Performance Testing

[0066] The cathode materials obtained in the above examples and comparative examples were subjected to scanning electron microscopy, X-ray diffraction analysis and surface Fe valence state analysis to obtain SEM images, X-ray diffraction patterns and Fe 2p spectra, respectively. Figure 1 The inorganic carbon composite sodium iron sulfate material prepared with the aid of reduced iron powder is spherical, with a particle size of about 20 μm. The X-ray diffraction spectrum is as follows Figure 2 As shown, all its peaks correspond to the standard card, proving that Na 2.6 Fe 1.7 (SO4)3 cathode material. Fe 2p spectrum is shown in Figure 3As shown in the figure, Figures (a) and (b) correspond to the corresponding materials obtained in Example 1 and Comparative Example 1. It can be seen from the figure that after adding reduced iron powder, the surface of the sample is all Fe 2+ , indicating that the Fe 2+ The ions are not oxidized, thus ensuring that the sample presents a good crystal structure without the generation of impurities; while in Comparative Example 1, Fe 3+ The content of Fe is 41.35%, indicating that a large amount of Fe 2+ The ions are oxidized, which leads to the appearance of impurities in the sample.

[0067] Application of cathode materials

[0068] The positive electrode materials obtained in the above examples and comparative examples were assembled into batteries: Under the condition of a dew point below -30°C, 0.0800g of the sodium iron sulfate positive electrode material obtained in this example or comparative example was weighed, 0.0100g of conductive carbon black as a conductive agent and 0.0100g of PVDF (polyvinylidene fluoride) as a binder were added, mixed evenly and coated on aluminum foil to make a positive electrode sheet, and in a vacuum glove box, a metal sodium sheet was used as the negative electrode, the battery separator was a Whatman GF / D glass fiber separator, and the electrolyte was 1mol / LNaClO4 (EC:DMC=1:1 (volume ratio) + 5% FEC) to assemble into a CR2025 button battery. Electrochemical performance tests and cycle performance tests were carried out in the range of 2 to 4.5V, specifically testing the first discharge capacity at 0.1C, the first coulomb efficiency, the discharge specific capacity at a current rate of 1C, and the capacity retention rate after 100 cycles. For specific results, see Figure 4 , 5 and Table 1.

[0069] Table 1 Electrical properties and cycle performance test results

[0070] Group Cathode Materials First capacitance at 0.1C First coulombic efficiency Discharge capacity at 1C Capacity retention rate 1 Example 1 93.89mAh / g 92.05% 89.48mAh / g 99.18% 2 Example 2 92.36mAh / g 91.76% 88.65mAh / g 99.02% 3 Example 3 91.36mAh / g 91.89% 87.23mAh / g 98.63% 4 Example 4 89.58mAh / g 92.33% 87.25mAh / g 99.14% 5 Comparative Example 1 76.01mAh / g 91.47% 71.41mAh / g 96.87% 6 Comparative Example 2 84.12mAh / g 89.28% 80.25mAh / g 96.92%

[0071] It can be seen from the above embodiments and battery performance tests that the reduced iron powder assisted preparation of inorganic carbon composite sodium ferric sulfate positive electrode material of the present invention has better electrical performance and cycle performance than the positive electrode material without reducing substances and adding reducing organic substances. The addition of reducing iron powder can not only ensure the reduction of trivalent iron, but also avoid the introduction of any impurities. The conventionally selected reducing organic substances, due to the low sintering temperature of the sodium ferric sulfate positive electrode material, are incompletely decomposed organic substances, and the technical effect of reducing iron powder assisted reduction cannot be achieved. In addition, in the preparation process, the raw materials used are easy to obtain, the processing process is relatively simple, environmentally friendly, and economical.

[0072] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A method for preparing an inorganic carbon composite sodium iron sulfate positive electrode material assisted by reduced iron powder, characterized in that: The method comprises the following steps: S1. Add sodium sulfate, ferrous sulfate and reduced iron powder into deionized water, stir until the sodium sulfate and ferrous sulfate are completely dissolved, and separate the remaining reduced iron powder to obtain a sodium ferric sulfate precursor solution; S2, mixing the sodium ferric sulfate precursor solution with an inorganic carbon source, stirring and then spray drying to obtain an inorganic carbon composite sodium ferric sulfate positive electrode material precursor; S3. Sintering the inorganic carbon composite sodium ferric sulfate positive electrode material precursor in an inert atmosphere to obtain an inorganic carbon composite sodium ferric sulfate positive electrode material.

2. The method for preparing inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reduced iron powder according to claim 1, characterized in that: The molar ratio of the reduced iron powder to ferrous sulfate is 0.0001-0.005:

1.

3. The method for preparing inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reduced iron powder according to claim 1, characterized in that: The inorganic carbon source is one or more of water-based carbon nanotube slurry, water-based graphene slurry, and water-based graphene nanoribbon slurry; the solid content of the slurry is 5-15%.

4. The method for preparing inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reduced iron powder according to claim 1, characterized in that: The mass ratio of inorganic carbon to sodium ferric sulfate in the inorganic carbon composite sodium ferric sulfate positive electrode material is 0.001 to 0.05:

1.

5. The method for preparing inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reduced iron powder according to claim 1, characterized in that: The concentration of the sodium iron sulfate precursor solution is 0.1-1.5 mol / L.

6. The method for preparing inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reduced iron powder according to claim 1, characterized in that: The process parameters of the spray drying process are: the frequency of the induced draft fan is 20-50 Hz, the feeding frequency is 5-15 Hz, the atomizer frequency is 200-400 Hz, the inlet air temperature is 200-280° C., and the outlet air temperature is 100-120° C.

7. The method for preparing inorganic carbon composite sodium ferric sulfate positive electrode material assisted by reduced iron powder according to claim 1, characterized in that: The sintering process in step S3 is as follows: In an inert atmosphere, the temperature is raised from room temperature to 300-450°C at a heating rate of 1-5°C / min and sintered for 8-12 hours.

8. The inorganic carbon composite sodium iron sulfate positive electrode material prepared by the method according to any one of claims 1 to 7, characterized in that: Its chemical formula is Na x Fe 3-0.5x (SO4)3 / C, where 2≤x≤2.

8.

9. The inorganic carbon composite sodium iron sulfate positive electrode material according to claim 8, characterized in that: The carbon composite sodium iron sulfate positive electrode material is a solid microsphere with a particle size of 10 to 30 μm.

10. A sodium ion battery, characterized in that: The positive electrode material of the sodium ion battery comprises the inorganic carbon composite sodium iron sulfate positive electrode material according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Sodium ferrous sulfate / carbon nanotube composite positive electrode material, preparation method and sodium ion battery

    CN115172724A

  • Preparation method of sodium ferrous sulfate / carbon composite positive electrode material, positive electrode material, positive electrode plate and sodium ion battery

    CN117154062A

  • Modified sodium ferric sulfate positive electrode material and preparation method thereof, and secondary battery

    CN118117067A

  • Pure-phase sodium ferric sulfate composite positive electrode material and application of sodium ion battery

    CN118412445A

  • Polyanion cathode active material and method for producing the same

    JP6180568B1

Cited By

  • Sodium ferric sulfate composite positive electrode material, preparation method thereof and sodium ion battery

    CN119943942A

  • Sodium ferric sulfate composite positive electrode material and preparation method thereof, and sodium ion battery

    CN119943942B